Experimental Study on the Behavior of Reinforced Concrete Derailment Containment Provisions under Quasi-Static Loads - Huy Q. Nguyen; Hoi Jin Kim; Nam-Hyoung Lim; Yun-Suk Kang; Jung J. Kim (Buildings, 2024)
Derailments pose a significant threat to high-speed rail safety. The development of effective derailment containment provisions (DCPs) that can be installed within a track gauge and withstand impact loads of derailed wheels while controlling the lateral movement of derailed trains is essential. This paper presents an experimental study on the behavior of reinforced concrete (RC) DCP systems under quasi-static loading. Three steel anchors were assessed for their performance and load-bearing capacity in a single-anchor test. Four full-scale DCP system tests were carried out to examine the effects of scenarios of impact load positions at the anchor and mid-span of the DCPs. The crack pattern, failure mechanism, load–displacement relationship, initial stiffness, and absorber energy capacity of the DCP specimens were acquired. The findings reveal that the failure mode of the DCP specimens was predominantly affected by the tension failure of the steel anchors. The load-carrying capacity and performance equivalent of the DCP system under the applied load scenarios significantly exceeded the design load, ranging from 125% to 168%. Also, the initial stiffness of the DCP system remains largely unaffected by the applied load positions, whereas the absorption energy capacity exhibits a contrasting trend.